2012
DOI: 10.1007/s11064-012-0941-8
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Morphine Administration Leads to Changes in Hippocampal BDNF Levels and Antioxidant Enzyme Activity in the Adult Life of Rats

Abstract: Objectives: It is know that repeated exposure to opiates impairs spatial learning and memory and that the hippocampus has important neuromodulatory effects after drug exposure and withdrawal symptoms. Thus, the aim of this investigation was to assess hippocampal levels of BDNF, oxidative stress markers associated with cell viability, and TNF-alpha in the short, medium and long term after repeated morphine treatment in early life. Methods: Newborn male Wistar rats received morphine (morphine group) or saline (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 71 publications
1
34
0
1
Order By: Relevance
“…Some factors of the immune system (such as TNF-α, IL-1β, IL-6, and NF-KB) show modifications due to chronic morphine exposure, and these modifications affect hippocampus function (45,46). In our study, TNF-α levels in parents that consumed morphine were measured 3 months after withdrawal.…”
Section: Discussionmentioning
confidence: 86%
“…Some factors of the immune system (such as TNF-α, IL-1β, IL-6, and NF-KB) show modifications due to chronic morphine exposure, and these modifications affect hippocampus function (45,46). In our study, TNF-α levels in parents that consumed morphine were measured 3 months after withdrawal.…”
Section: Discussionmentioning
confidence: 86%
“…Detection of alterations in glutathione levels with morphine treatment is frequent even at higher concentrations of the opioid (7,9,12,13) and can be evaluated by the quantitation of levels of sulfhydryl groups. Reduced glutathione is the major intracellular compound containing these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Rozisky et al observed that morphine treatment in early life in newborn male rats modulates brain-derived neurotrophic factor (BDNF) levels in the hippocampus (Rozisky et al, 2013). These changes may underlie behavioral alterations.…”
Section: Experimental Conditions In Rodentsmentioning
confidence: 99%